Penguatan Bidan Dalam Pelayanan Kesehatan Reproduksi Dan Keluarga Berencana Di Masa Pandemi Covid-19 - Eka Nur Rahayu; Fitriani Mediastuti (J.Abdimas: Community Health, 2021)
The pandemic COVID-19 has limited access to reproductive health and family planning services. This causes the coverage of family planning acceptors has decrease and reproductive health and family planning counseling is limited. Midwives are worried about security in providing services during a pandemic. Acceptors are afraid to come to health services for fear of contracting the corona virus. This service aims to provide education to midwives in Indonesia in providing reproductive health and family planning services during the pandemic. This service is a webinar. The webinar be held on November 20, 2020. Participants are midwives who are members of the Indonesian Akbidyo Alumni Association. The first theme of the webinar focused on models of reproductive health and family planning services during the pandemic. The second theme is about the REDI KB application which can facilitate reproductive health and family planning services by online. The results of the evaluation showed that the benefits of the application, discussion during the webinar, delivery of material, and the theme of the material were 93.75%; 92.5%, 93%; and 93.25%. The conclusion, this service activity is useful for midwives as a provision in providing health services in the pandemic. Midwives are expected to be able to take advantage of the REDI KB application which can be downloaded in the app store as an online counseling medium. In addition, midwives can also create convenient service flows for both midwives and patients by referring to the family planning service model during the pandemic.